M. Petr. Höchströms Missionarii und Pastoris in Galliwarn Beschreibung von dem unter Schwedischer Crone gehörigen Lappland : in sich fassend einen kurtzen Unterricht sowohl von des Landes Beschaffenheit überhaupt, als aüch von dem Züstande der Einwöhner, ihrer Haushaltung, Sitten, Manieren, Lebensart, Lastern und Aberglauben - Högström, Pehr, 1714-1784.; Neander, August, 1789-1850, former owner. IU-R; Gronau, Johann Hermann, 1708-1769, former owner. IU-R; Burrows, Roswell S., 1798-1879, former owner.; Lochner, Johann Friedrich, publisher.; Templin, translator.; Rochester Theological Seminary, former owner. IU-R (Stockholm, 1748)
Acquisition made accessible thanks to the generous support of the Frederick J. and Margret L. Worden Endowment. Ownership inscription of "C.L. Gronau" dated 1770 on front fly-leaf recto; "J.H. Gronau" inscribed on title page; bookplate on front paste-down: "Rochester Theological Seminary. Neander Library. Presented by Roswell S. Burrows, Esq." Head- and tail-pieces; initials. Signatures: A-U⁸ X⁴. Engraved title page on double leaves. Translation of: Beskrifning öfwer de til Sweriges krona lydande Lapmarker. Stockholm, 1747. Includes bibliographical references. Mode of access: Internet.